2005
DOI: 10.1186/1471-2431-5-40
|View full text |Cite
|
Sign up to set email alerts
|

Actuarial survival of a large Canadian cohort of preterm infants

Abstract: Background: The increased survival of preterm and very low birth weight infants in recent years has been well documented but continued surveillance is required in order to monitor the effects of new therapeutic interventions. Gestation and birth weight specific survival rates most accurately reflect the outcome of perinatal care. Our aims were to determine survival to discharge for a large Canadian cohort of preterm infants admitted to the neonatal intensive care unit (NICU), and to examine the effect of gende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
35
2
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 57 publications
7
35
2
2
Order By: Relevance
“…All four indices of lung profile showed that the male fetuses had less mature lungs than the females by approximately 1 wk (9). In a more recent and large cohort of births below 31 wk in Canada, Jones et al showed the familiar male/female differences in acute outcomes but interestingly showed that differences in survival were only apparent for infants born at 24-wk gestation (13). This is consistent with the thesis that the relative male immaturity determines the excess mortality observed in very preterm infants.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…All four indices of lung profile showed that the male fetuses had less mature lungs than the females by approximately 1 wk (9). In a more recent and large cohort of births below 31 wk in Canada, Jones et al showed the familiar male/female differences in acute outcomes but interestingly showed that differences in survival were only apparent for infants born at 24-wk gestation (13). This is consistent with the thesis that the relative male immaturity determines the excess mortality observed in very preterm infants.…”
Section: Discussionsupporting
confidence: 73%
“…The now routine use of antenatal corticosteroids and postnatal surfactant have been associated with a substantial improvement in survival (8,12,13). It may be therefore that there are less marked differences in outcome for boys and girls following the introduction of these treatments.…”
mentioning
confidence: 99%
“…Gebelik haftası 27-30 hafta arasında olan bebeklerin ölüm oranları diğer çalışmalara göre halen yük-sekti. Finlandiya'da bu oran %20, Kanada'da %5 iken bizim çalışmamızda %41.6 bulundu [6,10].…”
Section: Gebelik Haftasına Göre Ayrılmış Alt Gruplarda Morbidite Ve öLümunclassified
“…Ancak, preterm yenidoğanların sağ kalım ve klinik seyri farklı bölge ve hastanelerde çeşit-lilik göstermektedir. Pratik hayatta yapılan uygulamaların etkinliğini moniterize etmek için bu bebeklere ait güncel sürveyans çalışmalarını yapmak esastır [6]. Bu nedenle gelişmekte olan ülkelerde her bir bölge ve hastanenin kendisine ait preterm bebeklerin klinik seyrine dair verilerini değerlendirmesi önemlidir.…”
Section: Introductionunclassified
“…3 Published data from a large Canadian cohort show similar results. 4 Survival in recent years may have increased somewhat for the lowest gestational ages. At Yale-New Haven Children's Hospital, combined data for 2003 and 2004 showed survival to discharge was 38% for infants born at 23 completed weeks, 66% at 24 weeks and 71% at 25 weeks.…”
Section: Mortalitymentioning
confidence: 99%